Journal of modern literature - Temple University ([Bloomington, IN, etc., Indiana University Press, etc.], 1970)
"July issue is an Annual review supplement listing and describing publications of the previous calendar year."
Published: Philadelphia, PA : Temple University, 1970- ; Bloomington, IN : Indiana University Press, <2004- >
Academic Journal
Online version of print publication.
Keywords: Literature, Modern -- 20th century -- History and criticism -- Periodicals; Letterkunde; Histoire et critique